1989
DOI: 10.1037/0022-3514.56.2.228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coping skills training on generalized self-efficacy and locus of control.

Abstract: A number of studies have shown that mastery experiences strengthen self-efficacy expectancies that are specific to the mastery situation, rn this study I assessed the effects of cognitive-behavioral coping skills training on generalized expectancies concerning self-efficacy and locus of control in test-anxious college students. Compared with a waiting-list control group, the trained subjects exhibited significant decreases on trait and state measures of test anxiety and a higher level of academic performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
3
15

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(123 citation statements)
references
References 36 publications
6
99
3
15
Order By: Relevance
“…Bandura (1986) has questioned the value of general control beliefs because students may feel anxious about controlling one type of subject matter or performance setting (e.g., solving mathematical problems in a limited time period) but not others. In support of this contention, Smith (1989) found that locus of control measures did not predict improvements in academic performance or reductions in anxiety in highly self-anxious students who underwent an intensive coping skills training program, but self-efficacy scales did predict such improvements.…”
Section: Self-efficacy and Related Beliefsmentioning
confidence: 98%
“…Bandura (1986) has questioned the value of general control beliefs because students may feel anxious about controlling one type of subject matter or performance setting (e.g., solving mathematical problems in a limited time period) but not others. In support of this contention, Smith (1989) found that locus of control measures did not predict improvements in academic performance or reductions in anxiety in highly self-anxious students who underwent an intensive coping skills training program, but self-efficacy scales did predict such improvements.…”
Section: Self-efficacy and Related Beliefsmentioning
confidence: 98%
“…Actually, there is evidence that these control beliefs can be modified through training programs (Bandura, 1986;Eden & Aviram, 1993). Findings suggest that it is easier to change self-efficacy beliefs than locus of control (Smith, 1989) and that training affects specific efficacybeliefs more than general efficacy-beliefs (Schwoerer, May, Hollensbe, & Mencl, 2005). Therefore, training programs that enhance workers control beliefs may help protect employee health.…”
Section: Directions For Further Research and Practical Implicationsmentioning
confidence: 99%
“…The task-specific self-efficacy appraisal methods sometimes leave researchers with the false impression that beliefs of self-efficacy are only relevant in the context of carrying out a single minute task. Quite the contrary, however, self-efficacy researchers have acknowledged that one can face a wide range of tasks and situations with comparable self-efficacy and that perceptions of efficacy developed toward a particular task may generalize to other tasks of interest (Bandura, 1997;Pajares, 1996;Schunk & Swartz, 1993;Smith, 1989). Bong (1997) provided evidence that students' self-efficacy judgments contain strong subject-specific components.…”
Section: Between-domain Relations Of Motivation Constructsmentioning
confidence: 99%